2012
DOI: 10.1159/000339963
|View full text |Cite
|
Sign up to set email alerts
|

Insufficiency of Positron Emission Tomography and Magnetic Resonance Spectroscopy in the Diagnosis of Intravascular Lymphoma of the Central Nervous System

Abstract: Intravascular large B-cell lymphoma (IVL) is a rare type of extranodal lymphoma with an aggressive clinical course characterized by the proliferation of lymphoma cells within the lumen of small vessels. Diagnosis is often difficult because of marked variability in clinical presentation and nonspecific laboratory and radiological findings, especially when central nervous system (CNS) symptoms are the only manifestation. Modern metabolic imaging techniques such as positron emission tomography (PET) and 1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Several case reports have illustrated the added input of PET-CT to diagnose IVLBCL in the early stage ( 44 , 45 ). However, its low sensitivity makes it unfit for the evaluation of organ involvement, especially for central nervous system-localized disease (25% of all IVLBCL) ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have illustrated the added input of PET-CT to diagnose IVLBCL in the early stage ( 44 , 45 ). However, its low sensitivity makes it unfit for the evaluation of organ involvement, especially for central nervous system-localized disease (25% of all IVLBCL) ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some cases reported that a PET/CT scan might be insufficient for diagnosis of IVLBCL due to false negativity [22,23,24]. On the contrary, other reports suggest that a PET/CT scan may be useful for the diagnosis of IVLBCL even in hardly detectable lesions, such as the brain, meninges and vagina [25,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT imaging can be helpful in some cases but several studies have also suggested significant false negative results. [ 13 , 14 ] In our patient, PET/CT imaging was inconclusive and not helpful.…”
Section: Discussionmentioning
confidence: 72%